Academic staff perspectives on technology for assessment (TfA) in higher education: A systematic literature review - Devitt, Ann; Brady, Mairead (My University, 2019)
This paper presents a systematic literature review of academic staff experiences and perceptions of adopting Technology for Assessment OF/FOR/AS Learning in Higher Education. This paper is a qualitative synthesis of 65 peer‐reviewed journal articles published between 2012 and 2017 reporting on the use of technology for assessment (TfA). The results suggest that there are some efficiencies for staff in implementing TfA but this can come with a cost at the set‐up and maintenance phases. Furthermore, results indicated that assessment design is not of foremost concern to academic staff when introducing TfA, but that a wide variety of pressures and both educational and operational drivers are present. There were inconclusive findings in relation to understandings of appropriate institutional environments and supports for TfA to flourish in higher education. There is a need for empirical research, particularly longitudinal investigations, of academic experiences of implementations of TfA to investigate sustainability of adoption. The imperative of exploring the academic staff perspective as the instigator and manager of both the technology and the student learning experience requires deep consideration as TfA adoption progresses.
Keywords: Systematic literature review; Technology for assessment (TfA); Academic staff perspective; Digital Engagement